2013
DOI: 10.5012/bkcs.2013.34.12.3559
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Alumina-Grafted Manganese Oxide Particles Using Surfactants through Coprecipitation Method and Their Thermal Properties

Abstract: Alumina particles were grafted onto the surface of manganese oxide particles via the coprecipitation process using surfactant and cosurfactant. The phase of Mn/Al salts (Phase I) and the phase of precipitation agent (Phase II) were prepared in aqueous surfactant solution, separately. Phase II was added into Phase I and the reaction was performed to form the precursors of composites through hydrogen bonding between Mn(OH) 2 and Al(OH) 3 prepared by the reaction of Mn/Al salts with the precipitation agent. The a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 47 publications
(38 reference statements)
1
0
0
Order By: Relevance
“…The average pore sizes of the pristine and Mn-doped membrane active layers were 780 nm (Figure S1a) and 792 nm (Figure S1b), respectively. As shown in Figure 3, the Mn 2p3/2 spectrum showed two distinct peaks at 641.6 eV and 643.2 eV in the Mn-doped membrane layer, which were consistent with the binding energy of Mn(III) and Mn(IV) [25][26][27]. This demonstrated that the doped manganese in the Mn-doped membrane existed as two oxidation states (Mn 3+ and Mn 4+ ).…”
Section: Characterization Of Ceramic Membranessupporting
confidence: 68%
“…The average pore sizes of the pristine and Mn-doped membrane active layers were 780 nm (Figure S1a) and 792 nm (Figure S1b), respectively. As shown in Figure 3, the Mn 2p3/2 spectrum showed two distinct peaks at 641.6 eV and 643.2 eV in the Mn-doped membrane layer, which were consistent with the binding energy of Mn(III) and Mn(IV) [25][26][27]. This demonstrated that the doped manganese in the Mn-doped membrane existed as two oxidation states (Mn 3+ and Mn 4+ ).…”
Section: Characterization Of Ceramic Membranessupporting
confidence: 68%